The impact of institutional investors on dividend policy in South Africa - Mvovo, Sinesipho (Department of Finance and Tax, 2021)
Agency theory suggests that with enhanced monitoring, companies are more likely to pay out their free cash flow. Institutional investors may be great monitors given that they are professional investors with specialized expertise in evaluating firm's financial performance, management quality and governance. This study investigates the impact of institutional investors on dividend policy in South Africa, during the period from 2009 to 2018. Examining the effect of institutions as a whole can obscure the important variation in the subset of institutions, as they are not homogeneously incentivised to monitor firms. As a result, this paper segregates institutional investors into subcategories based on their monitoring abilities. Through the employment of a panel data regression model, this study finds a positive but statistically insignificant relation between institutional ownership and the dividend pay-out ratio; the positive relation is stronger in monitoring institutions. This paper used firm-fixed effect models to control for the possible endogeneity coming from unobserved firm-level, time invariant factors that determine both dividend policy and institutional ownership at the same time. The results of this paper do not support models that predict that institutional investors cause an increase in firm dividend pay-out ratio. Even though it is possible that firms pay dividends to reduce agency conflicts, this study did not find evidence that supports that the portion of shares held by institutional investors are related to the dividend pay-out policy. Secondly, although it is likely that institutions are more competent in monitoring management actions than individuals, there is no evidence to support that they use dividends as their monitoring device. The results of this study therefore caution those that invest in companies in South Africa and expect to receive more dividends by merely confirming the presence of institutional investors in their potential investee company.